2013
DOI: 10.18438/b8n89t
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Reading Buddies Program on Reading Level and Attitude Towards Reading

Abstract: Objective – This research examines the Reading Buddies program at the Grande Prairie Public Library, which took place in July and August of 2011 and 2012. The Reading Buddies program pairs lower elementary students with teen volunteers for reading practice over the summer. The aim of the study was to discover how much impact the program would have on participating children’s reading levels and attitudes towards reading. Methods – During the first and last sessions of the Reading Buddies program,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
1
1
0
1
Order By: Relevance
“…This trial has found that there was no evidence to suggest that mentoring is effective to increase reading enjoyment of students as their reading attitude get lower after intervention. This supported Dolman and Boyte-Hawryluk's study [38] in relation to the decrease of reading attitude. Nevertheless, this finding contradicted other studies [10], [12] which claimed that students showed more liking toward reading after getting intervention program.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…This trial has found that there was no evidence to suggest that mentoring is effective to increase reading enjoyment of students as their reading attitude get lower after intervention. This supported Dolman and Boyte-Hawryluk's study [38] in relation to the decrease of reading attitude. Nevertheless, this finding contradicted other studies [10], [12] which claimed that students showed more liking toward reading after getting intervention program.…”
Section: Resultssupporting
confidence: 85%
“…By contrast, the findings of an experimental study [38] suggested that reading attitude was even lower after mentoring intervention. However, this study involved only a small number of participants and used pre and post-test research group without control group; a study researching two groups with and without intervention may allow to establish whether differences between the two indicate clear effects of the mentoring intervention.…”
Section: Introductionmentioning
confidence: 80%
“…Bu nedenlerle öğrencilerden bazıları iyi okuma alışkanlıklarına sahipken, bazıları ise olması gerekenin dışında okuma alışkanlıkları sergileme eğilimindedir (Owusu-Acheaw & Larson, 2014). Özellikle ilkokul öğrencileri sosyo-ekonomik statü ve aile okuryazarlığı gibi dış etkenlerden kaynaklanan nedenlerle okumaya yönelik olarak olumlu tutumlar içinde olabilirler (Dolman & Boyte-Hawryluk, 2013). Okumaya yönelik olumlu tutum geliştiren iyi okurların okuduğunu anlama düzeyleri de yüksektir.…”
unclassified